Influence of mitochondrion-toxic agents on the cardiovascular system - Finsterer, Josef; Ohnsorge, Peter (Regulatory toxicology and pharmacology, 2013)
•Numerous agents are cardiotoxic due to disturbing mitochondrial functions.•Mitochondrion-toxic agents may cause myocardial/coronary artery damage or arrhythmias.•Discontinuation of cardiotoxic agents usually results in complete recovery. Cardiovascular disease may be induced or worsened by mitochondrion-toxic agents. Mitochondrion-toxic agents may be classified as those with or without a clinical effect, those which induce cardiac disease only in humans or animals or both, as prescribed drugs, illicit drugs, exotoxins, or nutritiants, as those which affect the heart exclusively or also other organs, as those which are effective only in patients with a mitochondrial disorder or cardiac disease or also in healthy subjects, or as solid, liquid, or volatile agents. In humans, cardiotoxic agents due to mitochondrial dysfunction include anthracyclines (particularly doxorubicin), mitoxantrone, cyclophosphamide, cisplatin, fluorouracil, imatinib, bortezomib, trastuzumab, arsenic trioxide, cyclosporine-A, zidovudine, lamotrigine, glycosides, lidocain, isoproterenol, nitroprusside, pivalic acid, alcohol, cocaine, pesticides, cadmium, mycotoxins, cyanotoxins, meat meal, or carbon monoxide. Even more agents exhibit cardiac abnormalities due to mitochondrion-toxicity only in animals or tissue cultures. The mitochondrion-toxic effect results from impairment of the respiratory chain, the oxidative phosphorylation, the Krebs cycle, or the β-oxidation, from decrease of the mitochondrion-membrane potential, from increased oxidative stress, reduced anti-oxidative capacity, or from induction of apoptosis. Cardiac abnormalities induced via these mechanisms include cardiomyopathy, myocarditis, coronary heart disease, arrhythmias, heart failure, or Takotsubo syndrome. Discontinuation of the cardiotoxic agent results in complete recovery in the majority of the cases. Antioxidants and nutritiants may be of additional help. Particularly coenzyme-Q, riboflavin, vitamin-E, vitamin-C, l-carnitine, vitamin-D, thiamin, folic acid, omega-3 fatty acids, and d-ribose may alleviate mitochondrial cardiotoxic effects.